2018
DOI: 10.20473/mog.v26i12018.26-28
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of pregnant women about anemia is related with adherence to iron tablets

Abstract: Objectives: to identify association between knowledge of pregnant women about anemia and the adherence to consume iron tablets in BPM Titik Suharti, Surabaya, IndonesiaMaterials and Methods: Observational analysis cross sectional study. Population consisted of 55 trimester pregnant women in BPM Titik Suharti, Surabaya, in March-April 2017. Samples were recruited using consecutive sampling. The number of sample was 35 respondents. Data were analyzed using chi-square test.Results: This research showed that all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The results of the current study are in line with another study conducted by Winardi & Andani (2018), which also showed that pregnant women with a good level of knowledge about anemia will take measures to prevent anemia (for example, consuming nutritious foods and regularly taking Fe tablets).…”
Section: Knowledgesupporting
confidence: 90%
“…The results of the current study are in line with another study conducted by Winardi & Andani (2018), which also showed that pregnant women with a good level of knowledge about anemia will take measures to prevent anemia (for example, consuming nutritious foods and regularly taking Fe tablets).…”
Section: Knowledgesupporting
confidence: 90%
“…Early information conveyed by health workers to pregnant women in this high-risk group can increase patient knowledge about risk of anemia and efforts to prevent it. Good knowledge can produce good attitudes and behaviors in using iron tablets for prevention of anemia during pregnancy [14,15]. Pregnant women in the western part of Indonesia were better than those in the eastern part at receiving iron tablets to prevent anemia during pregnancy [8].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about the importance of iron tablets during pregnancy has a significant relationship with the incidence of anemia in pregnant women [21]. Knowledge of pregnant women about anemia is significantly related to adherence to received iron tablets [14,15], adherence to receiving iron tablets is significantly related to the incidence of anemia in pregnant women [22], and also knowledge and attitudes towards iron supplements are strongly related to maternal behaviour pregnant in receiving iron tablets [23].…”
Section: Discussionmentioning
confidence: 99%
“…An iron supplementation program has widely been implemented in Indonesia, targeting female adolescents and pregnant women. However, this program phases many challenges: poor knowledge on anemia, low compliance of iron tablet consumption, low antenatal care visits, other micronutrient deficiencies, and poor health education [15,16]. Data from a basic health survey (2018) indicated that only 38.1% of pregnant women consumed the recommended iron tablets [5].…”
Section: Introductionmentioning
confidence: 99%
“…Data from a basic health survey (2018) indicated that only 38.1% of pregnant women consumed the recommended iron tablets [5]. Poor knowledge of the consequences of anemia was found to be associated with poor compliance with iron tablet consumption [15].…”
Section: Introductionmentioning
confidence: 99%